Emerging educational policy based on two indicators: monitoring the views of graduates and employers - Hermosillo-Richartt, Humberto (Universidad Autónoma de Tamaulipas, 2011)
Emerging educational policies, aimed at the improvement plans and programs of study include the fulfillment of two indicators: the follow-up study of graduates and employers opinion, this is essential to understanding the impact of education and generate information for decision making in carrying out substantive activities of the institutions of higher education. The graduate follow-up aims to determine the degree of satisfaction in terms of academic training received and employment status. The paper presents results of monitoring of graduates (2009) for the four undergraduate programs in the Facultad de Comercio y Administración de Tampico, of the Universidad Autónoma de Tamaulipas, and the employers’ view (2010), with a quantitative approach and a descriptive scope of vocational training, job characteristics and location in the labor market. Founded on the basic outline for graduate studies (1998) of the National Association of Universities and Institutions of Higher Education, the questionnaire format is redesigned and adapted to the requirements of the FCAT. The main results were: a degree of satisfaction of 75.3% in the race given; 70.26% overlap of work activity with a bachelor’s degree and 86.6% satisfaction of employers on the job performance of graduates from the FCAT.